2014
DOI: 10.1111/nyas.12451
|View full text |Cite
|
Sign up to set email alerts
|

The economics of restoration: looking back and leaping forward

Abstract: Since the publication of the Millennium Ecosystem Assessment in 2005 there has been a surge of interest in ecological restoration (ER) to recover biodiversity, re-establish ecosystem functioning and connectivity, and reactivate the delivery of ecosystem services. In policy spheres, there have also been repeated calls for expansion of restoration efforts. In many countries, new legislation now requires some form of restoration and/or a form of offset investment. All of this will require major increases in finan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 41 publications
2
31
0
Order By: Relevance
“…To fully evaluate the outcomes, all relevant variables, including the social ones, should be included. Barthélémy and Armani (2015) noted that social processes and local experiences are often ignored in restoration projects and Aronson et al (2010) and Blignaut et al (2013Blignaut et al ( , 2014 found that the benefits of restoration for society were not given due attention. In most of our case studies, however, the social component was fairly well included in the projects.…”
Section: Discussionmentioning
confidence: 99%
“…To fully evaluate the outcomes, all relevant variables, including the social ones, should be included. Barthélémy and Armani (2015) noted that social processes and local experiences are often ignored in restoration projects and Aronson et al (2010) and Blignaut et al (2013Blignaut et al ( , 2014 found that the benefits of restoration for society were not given due attention. In most of our case studies, however, the social component was fairly well included in the projects.…”
Section: Discussionmentioning
confidence: 99%
“…Only recently have ecologists begun to include economic and social considerations in the design of restoration projects (Blignaut et al 2014). With few exceptions, ecological restoration studies that include economics focus only on the cost side of restoration projects (Bullock et al 2011;Wilson et al 2012).…”
Section: Sayed Iftekhar Maksym Polyakov and Fiona Gibsonmentioning
confidence: 99%
“…Restoration projects, which are primarily aimed at restoring ecosystems of varying levels of degradation, are generally more costly than conservation projects, which are aimed at the protection of existing ecologically intact ecosystems (Blignaut et al 2014). Some types of costs are common for both restoration and conservation projects (e.g.…”
Section: Comparing Costs From Ecological Restoration and Conservationmentioning
confidence: 99%
“…Still lacking is knowledge related to the economics of restoration, an integration between the fields of restoration ecology and environmental economics (Blignaut et al, 2014;Wilson et al, 2012).…”
Section: Addressing Landscape Heterogeneitymentioning
confidence: 99%
“…These include restoration offsetting to compensate the impact of development activities on biodiversity and ecosystem services (BBOP, 2012;Blignaut et al, 2014;Gardner et al, 2013;Maron et al, 2012). Analysis on restoration offsetting in agricultural landscapes is rare compared with, for example, mining and urban development, which are generally less land-consumptive yet more profitable (Madsen et al, 2010).…”
Section: Leveraging Restoration Within Competing Land Usesmentioning
confidence: 99%